Hadis Mutawatir dan Hadis Ahad: Analisis Konseptual terhadap Otoritas Keduanya dalam Penetapan Hukum Islam - Hary Setiawan; Miftahul Huda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article examines the epistemological construction and authority of Mutawatir Hadith and Ahad Hadith in Islamic law determination amidst the currents of modern rationalism and skepticism. The main issue raised is the doubt of some circles regarding the validity of Ahad Hadith as a legal foundation due to the zhanni knowledge it produces, unlike Mutawatir Hadith which produces qath'i knowledge. This study aims to conceptually analyze the authority of both types of Hadith and their implications in istinbath ahkam. The method used is qualitative with a library research approach, analyzed through content analysis techniques in a descriptive-analytical manner. The results show that Mutawatir Hadith produces qath'i knowledge that becomes the fundamental foundation for aqidah and dharuri law, while Ahad Hadith produces zhanni knowledge that remains authoritative and obligatory to be practiced in the realm of furu' al-fiqh. The common ground between them lies in the obligation of verification through Jarh wa Ta'dil and 'Ilal al-Hadis, while the difference lies in the level of epistemological certainty, scope of application, and flexibility in the process of takhsis, nasakh, and ta'wil. A comprehensive understanding of the hierarchy of authority of both becomes an important instrument in facing the phenomenon of hadith rejection and information disruption in the digital era.